SHARIA VERSUS CONVENTIONAL STOCKS - Tomy Nurfajar; Rizky Nur Ayuningtyas Putri (FEBI Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
The capital market is an alternative source of funding for both the government and the private sector. Governments that need funds can issue bonds or debentures and sell them to the public through the capital market. Likewise, the private sector, in this case a company that needs funds, can issue securities, either in the form of shares or bonds, and sell them to the public through the capital market. One of the most popular instruments sold in the capital market is investing in shares, both sharia shares and non-sharia shares. In investing in the capital market, the important thing is to know the rate of return and risk in investing through technical analysis and fundamental analysis. This research analysis the comparison of returns, risks and coefficients of variation of sharia shares and non-sharia stocks in the Jakarta Islamic Index and IDX30 stock index on the Indonesia Stock Exchange (IDX). The analytical method used in this research is the mean difference test or t-test of two independent samples. The results of the t test for two independent samples show that the significance value of return and risk is 0.630 and 0.879, while the significance value of the coefficient of variation variable is 0.792, which means that all variables have a sig value > 0.05 and it can be concluded that there is no significant difference between return, risk and coefficient. Variations in sharia shares and non-sharia shares in the Jakarta Islamic Index (JII) stock index and the IDX30 stock index on the Indonesian Stock Exchange (IDX).